Identifying the critical phosphorus balance for optimizing phosphorus input and regulating soil phosphorus effectiveness in a typical winter wheat–summer maize rotation system in North China - Meng-ze XU; Yu-hong WANG; Cai-e NIE; Gui-pei SONG; Su-ning XIN; Yan-li LU; You-lu BAI; Yin-jie ZHANG; Lei WANG (Journal of Integrative Agriculture)
Phosphorus (P) is a nonrenewable resource and a critical element for plant growth that plays an important role in improving crop yield. Excessive P fertilizer application is widespread in agricultural production, which not only wastes phosphate resources but also causes P accumulation and groundwater pollution. Here, we hypothesized that the apparent P balance of a crop system could be used as an indicator for identifying the critical P input in order to obtain a high yield with high phosphorus use efficiency (PUE). A 12-year field experiment with P fertilization rates of 0, 45, 90, 135, 180, and 225 kg P2O5 ha−1 was conducted to determine the crop yield, PUE, and soil Olsen-P value response to P balance, and to optimize the P input. Annual yield stagnation occurred when the P fertilizer application exceeded a certain level, and high yield and PUE levels were achieved with annual P fertilizer application rates of 90–135 kg P2O5 ha−1. A critical P balance range of 2.15–4.45 kg P ha−1 was recommended to achieve optimum yield with minimal environmental risk. The critical P input range estimated from the P balance was 95.7–101 kg P2O5 ha−1, which improved relative yield (>90%) and PUE (90.0–94.9%). In addition, the P input–output balance helps in assessing future changes in Olsen-P values, which increased by 4.07 mg kg−1 of P for every 100 kg of P surplus. Overall, the P balance can be used as a critical indicator for P management in agriculture, providing a robust reference for limiting P excess and developing a more productive, efficient and environmentally friendly P fertilizer management strategy.